Influence of pH and Calcium Salts on Pythium Wilt Disease of Lettuce - Evan Tamayo; Shunping Ding (Plant Health Progress, 2026)
Pythium wilt of lettuce caused by the oomycete Globisporangium uncinulatum (syn. Pythium uncinulatum) has become a significant disease in commercial lettuce production in California. Calcium salts and their impact on soil pH are highly influential to the soil environment, and their manipulation has demonstrated significant effects on reducing diseases caused by several soilborne pathogens. The in vitro pH tolerance range of G. uncinulatum was assessed on corn meal agar (CMA), revealing its optimal growth at pH 5. Five salts, calcium acetate (Ca(C 2 H 3 O 2 ) 2 ), calcium propionate (Ca(C 2 H 5 COO) 2 ), calcium carbonate (CaCO 3 ), calcium chloride (CaCl 2 ), and calcium sulfate (CaSO 4 ) were tested in vitro on CMA with concentrations of 300, 600, and 1200 ppm for their suppressive effects against G. uncinulatum. Notably, calcium propionate and calcium acetate, common food preservatives, demonstrated significant inhibition of mycelial growth compared to the control (P < 0.001), with only slight reductions in pH, suggesting that the mycelial growth inhibition was due to compound-specific effects rather than pH change. Conversely, calcium chloride, calcium sulfate, and calcium carbonate showed no discernible reduction in mycelial growth. An in vivo pot trial found that when grown in inoculated soil, plants treated with calcium propionate, calcium carbonate, or calcium sulfate developed significantly greater root mass compared to the untreated control (P = 0.015). Amending soils with calcium salts and understanding their impacts on soil pH should be further studied as a promising effective and environmentally safe crop protection measure against Pythium wilt disease.